Banking Service and its Impact on the Macro Economy: A Comprehensive Review - Kumar , Shubham (Journal of Advanced Research in Accounting and Finance Management, 2023)
This comprehensive review explores the symbiotic relationship between banking services and the macro economy, delving into the multifaceted roles that banks play in shaping economic development and stability. The banking sector serves as a critical financial intermediary, channeling funds from savers to borrowers, thus facilitating efficient resource allocation. Moreover, banks are instrumental in capital formation, enabling the creation of physical and human capital that underpins economic growth. In addition to these roles, banks play an indispensable part in facilitating trade and commerce, providing essential credit to individuals and businesses, and transmitting monetary policy through interest rate adjustments. Their contribution extends to the development of payment and settlement systems that enhance economic efficiency and convenience. Regulatory policies wield substantial influence over the banking sector and the macro economy. Prudential regulations, interest rate policies, banking supervision, and consumer protection measures are pivotal in maintaining financial stability, ensuring fair banking practices, and protecting consumer interests. Effective crisis resolution mechanisms are essential to manage banking crises that may otherwise have far-reaching consequences on the broader economy. However, the contemporary banking sector faces a plethora of challenges in a rapidly changing global landscape. These challenges include technological disruption, cybersecurity threats, the evolving regulatory environment, globalization, and the persistent low-interest-rate environment. Navigating these challenges is crucial for banks to continue fulfilling their vital role in economic development and stability. The intricate interplay between banking services and the macro economy underscores the significance of ongoing research, adaptive policies, and industry resilience. As economies evolve, the banking sector must adapt and innovate to ensure its enduring contribution to the prosperity of nations.